Hands-On Science A Teacher's Guide to Student-Built Experiments and "The Exploratorium Science Snackbook." - Doherty, Paul.; Brown, Ruth; Exploratorium, Palo Alto, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
This booklet was written to help teachers climb out of their textbooks and join their students in discovering science for themselves. It features articles by elementary, middle, and high school teachers who have adapted hands-on science for their classrooms, and now teach science using interactive materials from "The Exploratorium Science Snackbook." Articles include: (1) "Getting Hands-On Science Into the Classroom"; (2) Building a Mini-Exploratorium"; (3) "Hands-On Science, In Class and Out"; and (4) "Making Your Own Science Exhibits." Eight science activities are presented. (PR)
Availability: Exploratorium Mail Order Dept., Box 21, 3601 Lyon Street, San Francisco, CA 94123 (
Sponsoring Agency: Fund for the Improvement and Reform of Schools and Teaching (ED/OERI), Washington, DC.
Sponsoring Agency: Eisenhower Program for Mathematics and Science Education (ED), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary School Science; Elementary Secondary Education; Experiential Learning; Hands On Science; Science Activities; Science Education; Science Instruction; Science Projects; Science Teachers; Secondary School Science; Reports, Research